2003
DOI: 10.1063/1.1592307
|View full text |Cite
|
Sign up to set email alerts
|

Contact resonances in voltage-modulated force microscopy

Abstract: A study of the frequency dependence of the signal in piezoresponse scanning force microscopy of ferroelectric materials has been performed. It is found that, for soft cantilevers, the signal is governed by the cantilever elastic properties. Both ferroelectric-electromechanical and electrostatic interaction contributions to the overall signal were found to depend on the frequency of the testing voltage. Indications for optimal measurement regimes are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 16 publications
0
107
0
Order By: Relevance
“…These frequency behaviors were explored by a number of authors. 95,[182][183][184] At low frequencies the frequency dispersion of the transfer function is relatively small and is primarily associated with the non-idealities of the cantilever design. Practically, variations of 10-20% (or more) are common, allowing establishing piezoelectric properties within this order of magnitude.…”
Section: Iic Complex Excitations and Spectroscopiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These frequency behaviors were explored by a number of authors. 95,[182][183][184] At low frequencies the frequency dispersion of the transfer function is relatively small and is primarily associated with the non-idealities of the cantilever design. Practically, variations of 10-20% (or more) are common, allowing establishing piezoelectric properties within this order of magnitude.…”
Section: Iic Complex Excitations and Spectroscopiesmentioning
confidence: 99%
“…The nonlocal electrostatic forces were studied by Harnagea et al, 95 who explored the frequency dependence of the piezoelectric and electrostatic contributions to the PFM signal, in addition to the effect of the loading force. Further work on exploring the signal formation mechanisms, resolution theory, cross-talk and environmental effects came from Kalinin and Jesse.…”
Section: Iia Basic Pfmmentioning
confidence: 99%
“…17,18,19 Imaging ferroelectric materials in the vicinity of a phase transition at small probing biases or imaging of biological systems with weak electromechanical coupling require optimal imaging conditions to be established, and a number of approaches based on using contact resonances in PFM have been suggested. 20,21 Finally, it is recognized that the use of the cantilever coupled with a beam-deflection detection system typical for most commercial AFM s does not allow longitudinal and normal force components to be unambiguously distinguished, 12,22 and it has been suggested that operation at specific frequencies would allow these components to be differentiated. 22 In our previous publications, we presented in-depth analysis of the static (low frequency) PFM imaging mechanism and demonstrated approaches for data interpretation and visualization.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been used in an exhaustive manner to understand nanoscale ferroelectric domain structure, 3-9 polarization relaxation, 10-14 domain-wall creep, 15 piezoelectric properties, [16][17][18][19][20] scaling effects, 17,21,22 reliability issues, 23,24 and properties of individual grains. 25 Although there are reports that correlate piezoresponse of the ferroelectric thin film to the possible crystallographic orientations, 7,26,27 there is scarce information on how the crystallography of each individual grain affects the polarization relaxation.…”
mentioning
confidence: 99%